2012
DOI: 10.1111/j.1462-5822.2011.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella type III effector SpvC, a phosphothreonine lyase, contributes to reduction in inflammatory response during intestinal phase of infection

Abstract: SummarySalmonella phosphothreonine lyase SpvC inactivates the dual-phosphorylated host mitogenactivated protein kinases (MAPK) through b-elimination. While SpvC can be secreted in vitro by both Salmonella pathogenicity island (SPI)-1 and SPI-2 type III secretion systems (T3SSs), translocation of this protein into the host cell cytosol has only been demonstrated by SPI-2 T3SS. In this study, we show that SpvC can be delivered into the host cell cytoplasm by both SPI-1 and SPI-2 T3SSs. Dephosphorylation of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 59 publications
4
74
1
1
Order By: Relevance
“…As for the ERK1/2, tyrosine phosphorylation at Tyr-205/Tyr-185 in ERK1/2 showed increased profiles (⌬ssaR/WT ϭ 0.54 and ⌬ssaR/WT ϭ 0.61) in RAW264.7 cells, although in HeLa cells the threonine phosphorylation site at Thr-190 on ERK2 showed the opposite trend (⌬ssaR/WT ϭ 1.96) ( Table I). This observation is consistent with the fact that an SPI2 phosphothreonine lyase SpvC dephosphorylates the threonine sites in ERK1/2 (47) to inactivate them, subsequently inducing antiinflammatory effect (48).…”
Section: Fig 2 Host Cell-specific Modulation Of Cellular Processes supporting
confidence: 85%
“…As for the ERK1/2, tyrosine phosphorylation at Tyr-205/Tyr-185 in ERK1/2 showed increased profiles (⌬ssaR/WT ϭ 0.54 and ⌬ssaR/WT ϭ 0.61) in RAW264.7 cells, although in HeLa cells the threonine phosphorylation site at Thr-190 on ERK2 showed the opposite trend (⌬ssaR/WT ϭ 1.96) ( Table I). This observation is consistent with the fact that an SPI2 phosphothreonine lyase SpvC dephosphorylates the threonine sites in ERK1/2 (47) to inactivate them, subsequently inducing antiinflammatory effect (48).…”
Section: Fig 2 Host Cell-specific Modulation Of Cellular Processes supporting
confidence: 85%
“…Recently, it was demonstrated that SpvC is translocated into the host cell cytosol through T3SS1 when bacteria are grown under SPI1-inducing conditions [319]. This effector has phosphothreoninelyase activity [318,320].…”
Section: Spvb and Spvcmentioning
confidence: 99%
“…SpvC specifically removes phosphate from threonine in the conserved activation loop motif TXY of ERK and inactivates this MAPK, and it is also active towards p38 and JNK in vitro [318,320]. Inactivation of MAPK is the proposed reason for the effect of SpvC in modulating host immune response by reducing inflammatory cytokines during the early stages of infection [319].…”
Section: Spvb and Spvcmentioning
confidence: 99%
“…Upon over expression, or in vitro, SpvC can target ERK1/2, p38 and JNK, 8,14 but in vivo, under physiological conditions, only ERK1/2 are dephosphorylated. 15 Genetic analyses show that SpvC is required for systemic infection in mice. 45 Inhibition of MAPK by SpvC reduces expression of pro-inflammatory cytokines (e.g., IL-8, TNFa) and diminishes inflammation and neutrophil infiltration at infection sites during early stages of infection.…”
Section: Salmonella Enterica Directly Activate and Repress Mapksmentioning
confidence: 99%
“…45 Inhibition of MAPK by SpvC reduces expression of pro-inflammatory cytokines (e.g., IL-8, TNFa) and diminishes inflammation and neutrophil infiltration at infection sites during early stages of infection. 14,15 In addition to ERK inhibition, S. enterica employ the AvrA effector to block JNK signaling. AvrA is a SPI1 T3SS effector protein that is a close homologue of YopJ.…”
Section: Salmonella Enterica Directly Activate and Repress Mapksmentioning
confidence: 99%